VALIDATED STABILITY INDICATING HPLC APPROACH FOR QUANTIFYING TRICHOLINE CITRATE AND CYPROHEPTADINE SIMULTANEOUSLY IN SYRUP FORMS - SAHAI, MOHINISH; DEVANNA, N. (International Journal of Applied Pharmaceutics, 2021)
Objective: This investigation demonstrates a stability-indicating and reliable “high-performance liquid chromatography” method to simultaneously quantify tricholine citrate (TEC) and cyproheptadine (CRH) in the syrup form and bulk form. Methods: Successful separation was accomplished using C18 “Agilent column (250 mm × 4.6 mm, 5 μm)” with isocratic type of elution using mobile phase containing 0.1 M NaH2PO4 buffer and acetonitrile at 55% volume and 45% volume ratio, respectively with 1.0 ml/min flow rate. The wavelength sensor was attuned at 263 nm to quantify TEC and CRH. Results: TEC and CRH peaks were eluted with fine resolution at retention times 1.837 min and 2.936 min, respectively. In the 137.5-412.5 μg/ml and 1-3 μg/ml concentration ranges for TEC and CRH, the calibration graphs were linear, with regression coefficients of 0.9999 and 0.9998, respectively. The suggested "high-performance liquid chromatography" approach has been shown as sensitive, precise, robust, accurate, specific and stability indicating through the resolution of TEC and CRH from its degradation-based compounds. Conclusion: The established high-performance liquid chromatography technique was effectively extended to the evaluation of TEC and CRH in the combined syrup form and the test results appeared satisfactory.